To investigate the structural, electronic, optical and magnetic properties of Sr-doped KNbO3 for perovskite solar cell applications: A DFT study - Jameel, Muhammad Hasnain; Rehman, Azka Rehman; Roslan, Muhammad Sufi; Agam, Mohd Arif (2023)
A First-principles research based on density functional theory is used to explore the various properties of pure and Sr-doped-KNbO3-perovskites compounds such as structural, electronic, magnetic, and optical characteristics. The Sr impact on structural, optical, electronic, and magnetic properties of Sr-doped-KNbO3 are investigated using ultra-soft pseudo-potential. The band gap of Sr-doped-KNbO3 is found to be remarkably increased from 1.50 eV to 1.83 eV after the doping of Strontium (Sr)with various percentages(0%, 12.5%, 25%, 37.5%). Under the DFT study, strontium (Sr) is appropriate material for increasing the band gap of KNbO3. Owing to the difference in ionic radii of Mo and Sr volume of crystal cells also decreased from 82.68 to 42.89 A3 after the doping of Strontium (Sr). The bandgap nature is found indirect furthermore bandgap showed that the material is a prominent semiconductor. A significant increment is obtained in the optical conductivity and also bandgap. After the doping of strontium (Sr)impurities, the energy absorption peaks are amplified. It is also observed that due to Sr substitution optical conductivity shifted toward higher energies. Sr-doped-KNbO3 has enhanced optical conductivity, energy absorption, and refractive index, making it an appropriate material for perovskite solar cell applications.